Breaking Immunological Tolerance in Systemic Lupus Erythematosus - Pieterse, Elmar; van der Vlag, Johan (Frontiers in Immunology, 2014)
Systemic Lupus Erythematosus (SLE) is a fairly heterogeneous autoimmune disease with a highly complex and not completely known etiology that mainly affects women in the childbearing age. SLE is a prototype type III hypersensitivity reaction in which immune complex depositions cause inflammation and tissue damage in multiple organs. Two distinct cell death pathways, apoptosis and NETosis, are central and crucial processes in the pathogenesis of SLE. There is growing evidence that histone modifications induced by these cell death pathways exert a key role in the induction of autoimmunity. In the current review, we discuss how abnormalities in apoptosis, NETosis and histone modifications may lead to a break of immunological tolerance in SLE.